Collection de livres électroniques en français basée sur l'application mobile de Microsoft PowerPoint - Christian Arvi Alfian; Dwi Astuti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
Reading is one of the skills that language learners must learn, in French. Lack of reading time has an impact on students' low interest in reading. This affects students' ability to read. For this reason, it is necessary to maintain and increase reading interest to achieve learning objectives, one of which is by providing electronic reading materials in the form of flipbooks. This study aims to describe the needs of teachers and students as well as produce electronic books in the form of flipbooks for French reading skills in Class XI SMA. This research uses the Research and Development (R&D) level 1 method as proposed by Sugiyono. The stages of this research include data collection through questionnaires, product design, design validation, and design revision. Based on the results of the analysis of the needs of teachers and students, an initial product was made which was then assessed by the validator. Based on the input from the validators, a revised product (final product) was made in the form of an e-book in the form of a simple flipbook using the Microsoft PowerPoint application which contains reading material following the French syllabus of the SMA Class XI accompanied by practice questions.